VD_FINDINFO HC / 2015 / 679 vom 19. Juni 2015 - VD Tribunal cantonal (2015)
BAIL À LOYER, ANNULABILITÉ, RÉSILIATION, PRINCIPE DE LA BONNE FOI, LOYER USUEL | 271 al. 1 CO, 271a al. 1 let. b CO, 11 al. 1 OBLF